The Social-Psychological And Pedagogical Aspects Of Acmeology - Hakobyan, Greta; Hovhannisyan, Arusyak; Sisyan, Susanna (Զանգակ հրատ.)
Acmeology is an anthropological science, which studies person's spiritual, intellectual, physical, as well as individual, personal and professional development features, factors and patterns during his life maturity. The article describes the methodological bases of acmeology, its development stages, branches, scientific-practical problems related to the improvement of a person during his professional activity and the highest manifestation of his vital potential. Theoretical and practical issues of andragogy are interpreted based on the analysis of social survey data.
Keywords: Pedagogy